1992
DOI: 10.1021/bi00148a031
|View full text |Cite
|
Sign up to set email alerts
|

Polarity of lipid bilayers. A fluorescence investigation

Abstract: Through steady-state and time-resolved fluorescence experiments, the polarity of the bilayers of egg phosphatidylcholine vesicles was studied by means of the solvatochromic 2-anthroyl fluorophore which we have recently introduced for investigating the environmental micropolarity of membranes and which was incorporated synthetically in phosphatidylcholine molecules (anthroyl-PC) in the form of 8-(2-anthroyl)octanoic acid. Fluorescence quenching experiments carried out with N,N-dimethylaniline and 12-doxylsteari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 57 publications
2
57
1
Order By: Relevance
“…The precise orientation and location of the NBD group of this molecule in the membrane is known London, 1987, 1988;Mitra and Hammes, 1990;Wolf et al, 1992;Abrams and London, 1993). This group has been found to be localized at the membrane interface which has unique motional and dielectric characteristics distinct from both the bulk aqueous phase and the hydrocarbon-like interior of the membrane (Seelig, 1977;Ashcroft et al, 1981;Stubbs et al, 1985;Perochon et al, 1992;Slater et al, 1993;Venable et al, 1993;White and Wimley, 1994;Gawrisch et al, 1995) thus making it an ideal probe for monitoring red edge effects. Furthermore, previous electrophoretic measurements have shown that the NBD group in NBD-PE is uncharged at neutral pH in the membrane (Chattopadhyay and London, 1988).…”
Section: The Wavelength-selective Fluorescence Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…The precise orientation and location of the NBD group of this molecule in the membrane is known London, 1987, 1988;Mitra and Hammes, 1990;Wolf et al, 1992;Abrams and London, 1993). This group has been found to be localized at the membrane interface which has unique motional and dielectric characteristics distinct from both the bulk aqueous phase and the hydrocarbon-like interior of the membrane (Seelig, 1977;Ashcroft et al, 1981;Stubbs et al, 1985;Perochon et al, 1992;Slater et al, 1993;Venable et al, 1993;White and Wimley, 1994;Gawrisch et al, 1995) thus making it an ideal probe for monitoring red edge effects. Furthermore, previous electrophoretic measurements have shown that the NBD group in NBD-PE is uncharged at neutral pH in the membrane (Chattopadhyay and London, 1988).…”
Section: The Wavelength-selective Fluorescence Approachmentioning
confidence: 99%
“…This not only results in the anisotropic behavior of the constituent lipid molecules, but more importantly, the environment of a probe molecule becomes very much dependent on its precise localization in the membrane. While the center of the bilayer is nearly isotropic, the upper portion, only a few angstroms away toward the membrane surface, is highly ordered (Seelig, 1977;Ashcroft et al, 1981;Stubbs et al, 1985;Perochon et al, 1992;Slater et al, 1993;Venable et al, 1993;White and Wimley, 1994;Gawrisch et al, 1995). As a result, properties such as polarity, fluidity, segmental motion, ability to form hydrogen bonds and extent of solvent (water) penetration would vary in a depth-dependent manner in the membrane (Fig.…”
Section: Wavelength-selective Fluorescence As a Membrane Dipstickmentioning
confidence: 99%
See 1 more Smart Citation
“…While the center of the bilayer is nearly isotropic, the upper portion, only a few angstroms away toward the membrane surface, is highly ordered. 38,[101][102][103][104][105] Properties such as polarity, fluidity, segmental motion, ability to form hydrogen bonds and extent of solvent penetration vary in a depth-dependent manner in the membrane. The interfacial region in membranes is the most important region so far as the dynamics and function of the membrane is concerned.…”
Section: Membrane Interface: An Appropriate System For the Rees Approachmentioning
confidence: 99%
“…The membrane interface is characterized by unique motional and dielectric characteristics distinct from both the bulk aqueous phase and the more isotropic hydrocarbon-like interior of the membrane. [101][102][103][104]106 It is a chemically heterogeneous region composed of lipid headgroup, water and portions of the acyl chain. 107 Overall, the interfacial region of the membrane accounts for 50% of the thermal thickness of the bilayer.…”
Section: Membrane Interface: An Appropriate System For the Rees Approachmentioning
confidence: 99%